JUDICIAL CONSIDERATIONS REGARDING THE CRIMINAL ACT OF STREET ROBBERY (IN THE CASE OF DECISION NUMBER 380/PID.B/2025/PN MDN) - Syadar Saragih; Muhammad Hizbullah (CV. Barokah Publsiher, 2026)
Street robbery (begal) is a form of street crime that increasingly disturbs the public because it is carried out through violence or threats of violence in public spaces. In Indonesian positive criminal law, begal is not regulated as a separate offense, but is classified as theft with violence as stipulated in Article 365 of the Indonesian Criminal Code (KUHP). This study aims to analyze the legal construction of the crime of begal and to examine the judge’s legal considerations in Decision Number 380/Pid.B/2025/PN Mdn using a normative legal research method based on statutory, case, and conceptual approaches. The results of the study show that the legal construction of the crime of begal is formed by the elements of theft, violence or threats of violence, and aggravating circumstances as regulated in Article 365 paragraph (2) of the KUHP. In Decision Number 380/Pid.B/2025/PN Mdn, the panel of judges analyzed all elements of the offense systematically based on the facts revealed at trial and valid evidence. The judges’ considerations in rendering the decision reflect the principles of justice, legal certainty, and expediency through consistent and transparent application of the law, as well as the imposition of a proportional sentence that takes into account the interests of the victim and the rights of the defendant.